High-speed graphene@Ag-MnO2micromotors at low peroxide levels - Ye, H.; Kang, J.; Ma, G.; Sun, Hongqi; Wang, Shaobin (Academic Press, 2018)
Platinum (Pt) free micro/nanomotors (MNMs) using a low content of fuels are highly desired for many applications. Herein, we demonstrate that cathodic electrofabrication can produce modified MnO 2 based microtubes and microrods as highly efficient MNMs in hydrogen peroxide (H 2 O 2 ) as low as 0.2%. The speed of graphene/Ag-MnO 2 micromotors could be smartly regulated using a surfactant and the maximum speed of an individual micromotor exceeds 1.3 mm s -1 in 0.5% H 2 O 2 . The propelling force and output power of the micromotors are 3.4 and 10 times as high as those of the best Pt-based micromotors reported. These Ag-MnO 2 based micromotors are envisioned to be a great promise for practical applications from biomedical delivery to environmental decontamination.